Current and emerging pharmacotherapy for pediatric allergic rhinitis. (3rd May 2021) - Tomazic, Peter Valentin; Lang-Loidolt, Doris
ABSTRACT: Introduction: Allergic rhinitis (AR) is a global health problem in adults as well as the younger population, continuously increasing and posing a significant problem for patients, health care systems and economies. For the younger population, some aspects differ from treatment of adults, namely, prevention, compliance and adherence. Areas covered: This narrative review summarizes all the pharmacotherapeutic options with special focus on the pediatric population. Moreover, it elucidates prevention strategies as well as future developments of AR treatment. Currently, symptomatic therapy in the form of steroids and antihistamines is applied topically and systemically where steroids need to be administered with caution and for a very short term. The only disease-modifying and causal treatment is allergen immunotherapy administered sublingually and subcutaneously. Future and current novel therapeutic options are human monoclonal antibodies. Expert opinion: The greatest potential for future developments currently lie in allergen immunotherapy and here in different routes of administration and modification of (recombinant) allergens as well as immune‐modulating adjuvants and nanoparticles. Secondly, monoclonal antibodies are promising molecules blocking and/or interfering with up- and downstream immune mechanisms. Another important aspect lies in prevention of allergic sensitization and disease progression through both AIT and biologics which is particularly true for the pediatric population.